2022
DOI: 10.1108/ijefm-10-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Making or remaking people and places through festivals: an island tourism perspective

Abstract: PurposeThis study aims to investigate two festivals that are held annually in Hong Kong, to explore the essence of festival meanings – the extent to which the perceived sociocultural benefits of festivals articulate the production of a sense of place (SOP) and its respective locality.Design/methodology/approachThe study utilises a comparative analysis approach to examine visitors’ views of the festivals. It constructs a theoretical framework of the interaction mechanism between tourism and place evolution by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Bulchand-Gidumal [26] discussed the post-COVID-19 recovery of island tourism using a smart tourism destination framework, in which the dimensions of smart sustainability include sustainable infrastructure, sustainable destination planning, and sustainable tourism economies. Li and Lau [27] explored how the perceived sociocultural benefits of festivals articulate island tourism's production of a sense of place and its respective locality. Zhao et al [28] found that there are recreational and cultural ecosystem service values for island tourism.…”
Section: The Initial List Of Sustainable Island Tourism Evaluation Cr...mentioning
confidence: 99%
“…Bulchand-Gidumal [26] discussed the post-COVID-19 recovery of island tourism using a smart tourism destination framework, in which the dimensions of smart sustainability include sustainable infrastructure, sustainable destination planning, and sustainable tourism economies. Li and Lau [27] explored how the perceived sociocultural benefits of festivals articulate island tourism's production of a sense of place and its respective locality. Zhao et al [28] found that there are recreational and cultural ecosystem service values for island tourism.…”
Section: The Initial List Of Sustainable Island Tourism Evaluation Cr...mentioning
confidence: 99%
“…Most students creatively change their work based on assignments and problem-solving. Some of these changes affect the performance of the work, and others affect the appearance of the work so students can use their imagination to the fullest(Lau & Li, 2022). The challenge of the problems was similar (p=0.028>0.01), possibly due to the incorrect configuration of the process tasks.…”
mentioning
confidence: 99%